The Experimental Study of the Effects of Silica-gel Bed Thickness on The Regeneration Process in a Desiccant Column - waleed abdali; Abdulsalam D.M. Hassen (Wasit Journal of Engineering Sciences)
A desiccant column contains a silica gel as a solid moisture absorbent material has been used in this study, in which the regeneration or desorption process was discussed. The dimensions of the silica-gel column are 30 cm long*30 cm wide with three thickness of desiccant bed (5,10, &15) cm, respectively. The mass flow rate and the inlet temperature of the regeneration air used are 3.72 kg/min and 53 °C respectively. This air was obtained using solar air heater in addition to an electric heating unit for temperature control purpose. The results obtained showed that the regeneration period is affected by the bed thickness. Increasing the bed thickness of silica increase the regeneration period and vice versa For example, the complete drying process of silica gel from moisture took 21 min with thickness of bed (5 cm), while it took 42 min with thickness of bed (15 cm)